PENATALAKSANAAN FISIOTERAPI ULTRA SOUND DAN TERAPI LATIHAN PADA KASUS CARPAL TUNNEL SYNDROME SINISTRA DI RSUD PROF. Dr. MARGONO SOEKARJO PURWOKERTO - Vega Indra Utama; Nur Susanti (LPPM Universitas Pekalongan, 2014)
Abstract Carpal tunnel syndrome is a symptom that occurs due to the emphasis on N. The median is the cause of repetitive motion or trauma. The objectives to be achieved, namely, reduce pain, increase range of motion, increase muscle strength, and enhance the functional activity of the patient. The objectives are: increase muscle strength in the left wrist area, increase range of motion left wrist, and restore functional activity with respect to the functional activity of the left hand. In helping to overcome these problems can be used modalities of ultrasound physiotherapy and exercise therapy. And the results obtained at the end of therapy include: increased muscle strength, increase range of motion, and the enhancement of functional activity. Based therapy is carried out for 6 times to get the following results: (1) an increase in muscle strength of dorsal flexion of T1 to T6 = 4 = 5, Palmar flexion T1 to T6 = 3 = 4, (2) an increased range of motion Active dorso palmar flexion T1 = 50 º -0 º -55 º to T6 = 50 º -0 º -60 º. Keywords: Carpal Tunnel Syndrome Sinistra with U.S. modalities (ultra sound) and exercise therapy.